Understanding PHP data objects (PDO) - Stone River eLearning; Safari eBooks ([S.I.] : Stone River eLearning, 2014)
"In this course you will learn PHP Data Objects (PDO) and how this library written in PHP works with databases. While a basic knowledge of PHP is recommended for this course, both beginners and experienced web developers will gain a complete understanding of how PHP Data Objects work. Exactly What Is PHP Data Objects? The PHP Data Objects (PDO) extension defines a lightweight, consistent interface for accessing databases in PHP. Each database driver that implements the PDO interface can expose database-specific features as regular extension functions. Note that you cannot perform any database functions using the PDO extension by itself; you must use a database-specific PDO driver to access a database server. PDO provides a data-access abstraction layer, which means that, regardless of which database you're using, you use the same functions to issue queries and fetch data. PDO does not provide a database abstraction; it doesn't rewrite SQL or emulate missing features. You should use a full-blown abstraction layer if you need that facility."--Resource description page.
Title from resource description page (viewed Nov. 10, 2014).
Presenter, Stone River eLearning.
Keywords: PHP (Computer program language); Open source software; Electronic books